IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) DI DISTRIK NINIA KABUPATEN YAHUKIMO PROVINSI PAPUA - Noto Kobak (JURNAL KEBIJAKAN PUBLIK, 2020)
Village Fund Allocation (ADK) basically can trigger independent village government in managing potential and resources. Regulations made by the village government in this case must reflect community involvement. Regulations must regulate institutionalization that ensures the public can participate in development programs. Data from the Central Bureau of Statistics for Yahukimo Regency in 2018 shows that all villages in Ninia District are independent villages, where almost all of the people are able to meet their needs by holding them independently. The purpose of this research is to know and describe the implementation of ADK in detail as well as to find out the supporting and inhibiting factors for implementing ADK policies in Ninia District, Yahukimo Regency. This type of research is descriptive with a qualitative paradigm. Location in the District Government of Ninia, with the consideration that the location is easy to reach. Focus on describing the implementation of the Village Fund Budget (ADK) policy in Ninia District, Yahukimo Regency. Sources of data were obtained from primary data obtained directly from the source, namely the Head of the Ninia District, the Secretary of the District of Ninia, the District Staff of Ninia and the Head of the Ninia Village and the Village Apparatus. Secondary data were obtained from documents, records and reports. Collection techniques using observation, interviews, documentation and literature study. Data analysis consisted of reduction, presentation and conclusion drawing. The results showed that the ADK policy communication was carried out between the village administration and the community components or traditional institutions. All resources play an important role in minimizing resistance to the development planned by the government. In terms of disposition, the leadership involved village institutions in all stages of allocation. The policy bureaucratic structure depended on the guidelines and aspects of the involvement of all parties. ADK is used for physical developments such as housing and clean water facilities to meetthe needs of the population